Utilizing the Scramble Method to Develop Arabic Writing Proficiency in Grade IV Students of MIN 1 Palu - Maharani, Putri; Andi Anirah; Harun, Ubay (Program Studi Pendidikan Bahasa Arab (PBA), Universitas Islam Negeri Datokarama Palu, 2025)
This study aims to describe how the Scramble Method is implemented in training the Arabic writing skills of Class IV students at MIN 1 Palu City. It also describes the obstacles and solutions related to the implementation of the Scramble Method in training the Arabic writing skills of Class IV students at MIN 1 Palu City. This study uses a descriptive qualitative approach. Data collection techniques include observation, interviews, and documentation, with triangulation techniques used to test the validity of the data. The data of this study were analyzed through data reduction, data display, and verification (conclusion drawing verification). Meanwhile, the subjects of the study were Arabic subject teachers and Class IV students at MIN 1 Palu City. The results of this study indicate that the application of the Scramble Method in training the Arabic writing skills of Class IV students at MIN 1 Palu City was carried out in three stages: (1) Preliminary Activities, (2) Core Activities, and (3) Closing Activities. The challenges associated with the scramble learning method include the complexity of creating the media, the extended time needed for learning, and the generation of distracting noises. To address these challenges, the teacher can announce the creation of study groups during the previous class to optimize time usage. Additionally, the teacher should clarify the learning rules and encourage students to maintain a positive and enthusiastic attitude toward learning.